2023
DOI: 10.1186/s40854-023-00472-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic portfolio choice with uncertain rare-events risk in stock and cryptocurrency markets

Abstract: In response to the unprecedented uncertain rare events of the last decade, we derive an optimal portfolio choice problem in a semi-closed form by integrating price diffusion ambiguity, volatility diffusion ambiguity, and jump ambiguity occurring in the traditional stock market and the cryptocurrency market into a single framework. We reach the following conclusions in both markets: first, price diffusion and jump ambiguity mainly determine detection-error probability; second, optimal choice is more significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…The study concludes that no evidence suggests cryptocurrency is a strong or weak safe haven for the traditional market. In managing investment risk arising from market uncertainty, Lv et al (2023) found evidence to support the conclusion that price diffusion ambiguity is critical in influencing investor portfolio decisions, especially during rare events, in both markets.…”
Section: Cryptocurrency Market Interconnectedness With Traditional Fi...mentioning
confidence: 85%
“…The study concludes that no evidence suggests cryptocurrency is a strong or weak safe haven for the traditional market. In managing investment risk arising from market uncertainty, Lv et al (2023) found evidence to support the conclusion that price diffusion ambiguity is critical in influencing investor portfolio decisions, especially during rare events, in both markets.…”
Section: Cryptocurrency Market Interconnectedness With Traditional Fi...mentioning
confidence: 85%
“…Other authors proposed to tackle the problem on different grounds, for example by incorporating the occasional presence of rare events [11] or phrasing it as a sorting problem [4]. Some even tried incorporating volatility as an additional asset [10].…”
Section: Introductionmentioning
confidence: 99%